Health-Promoting Lifestyles and Awareness of Diabetes in Adults with Type 2 Diabetes in Jordan - Alkhawaldeh, Omar; Shoqirat, Noordeen; Abu-Sheikh, Buthina; Froelicher, Erika (Jordan Medical Journal, 2023)
Aim: This study evaluates the association between health-promoting lifestyles and diabetes knowledge with glycemic control in adults with type 2 diabetes. Methods: This cross-sectional study employed convenience sampling and a structured interview questionnaire consisting of the following measures: demographic and clinical characteristics, Health Promotion Lifestyle Profile II, diabetes knowledge questionnaire, and laboratory measurements. Descriptive and inferential statistics were used to analyze the data. Results: The study included 248 participants recruited from four public hospitals. The results indicated a deficit in several aspects of diabetes knowledge and a suboptimal adoption of health-promoting lifestyles. The findings showed that 81.5% of the sample had non-optimal glycemic control as measured by glycosylated hemoglobin (HbA1c) level. Health-promoting lifestyles predicted optimal glycemic control, while insulin use was a statistically significant predictor for non-optimal glycemic control. Conclusion: Most participants did not have their diabetes controlled and their diabetes knowledge and health-promoting lifestyles were suboptimal. Health promotion education and strategies to enhance health-promoting lifestyles and diabetes management are essential to patients so that they become confident about managing their diabetes.